LEGAL RISKS OF AN EMPLOYEE WHEN INCLUDING A BONUS AS AN INCENTIVE (STIMULATING) PAYMENT IN THE ACTUAL SALARY AND THE PROSPECTS OF RECOVERY IN A COURT OF LAW - STRELNIKOV S.V. (Legal Bulletin)
The relevance of this study lies in the impossibility for an employee to recover unpaid incentive (stimulating) payments (bonuses) from the employer in the vast majority of court disputes due to a number of different problems, which entails a violation of the employee’s right to timely and fair wages as a universally recognised right protected by international and Russian legislation. The main purpose of the study is to identify, analyse and assess the legal risks for the employee in the wording of standard bonus criteria and other provisions of local regulatory acts of employers establishing the system of remuneration of labour, in relation to the prospects of recovery in court. It also analyses judicial practice on disputes on the recovery of incentive payments, legal regulation of this institution in the Russian Federation with the identification of shortcomings, problems, gaps, which are inherent in labour legal relations at the current stage of development with the development of proposals to improve legal regulation and law enforcement practice in this area. The problems under consideration are expressed in the abuse of the right by the employer in the form of fictitious bonuses (usually premiums), which are actually part of the salary, as well as in the formulation of general and subjective criteria for labour evaluation in local regulations, due to which in practice it is difficult for an employee to justify the amount of the bonus, to substantiate the right to it and to recover it in court, which is also facilitated by the formal consideration of this category of disputes by Russian courts. The methods used in this study are general scientific (analysis, analogy, deductive and inductive methods) and special (formal legal) methods of cognition. The conclusions of this study are as follows: the author believes that it is the imperfection of labor legislation, as well as the formal approach of the courts to this category of disputes lead to the possibility of abuse of the right on the part of the employer for non-payment of incentive (stimulating) payments. On the basis of the analysis of the research problems the assessment of typical wording of bonus criteria in local normative acts on the possibility of collecting the bonus in court in case of its nonpayment and related legal risks was carried out. Emphasis is also placed on the prospects of collecting the bonus due to its non-payment in case of dismissal, including taking into account the specifics of labor (position, industry of labor). Based on various typical circumstances of this category of disputes, the prospects of judicial recovery of unpaid bonuses are revealed. Practical recommendations for proving fictitious bonuses in court and improving normative legal regulation in this area have been developed.